Implementation of Soft Loan Disbursement for Micro Enterprises and Cooperatives Affected by Covid-19 Viewed from the Precautionary Principle: Implementasi Penyaluran Pinjaman Lunak Bagi Usaha Mikro dan Koperasi Terdampak Covid-19 Ditinjau dari Prinsip Kehati-Hatian - Fathan, Muhammad Haikal (Annual Review of Legal Studies, 2024)
In order to handle the economic impact in Rembang Regency, the Rembang Regency government is providing stimulus in the form of strengthening business capital to MSMEs and micro actors who are affected by the economic impact due to Covid-19 in Rembang Regency. by assigning the Regional Owned Enterprise PD BPR BKK Lasem to carry out soft loans for micro businesses and cooperatives. The problems studied include 1.) How to implement the Rembang Regent's regulation No. 44 of 2020 concerning soft loans for micro businesses and cooperatives affected by Corona Virus Disease 2019 (Covid-19) through assignments to PT. BPR BKK Lasem (Perseroda) in Rembang Regency; 2.) How is the The distribution of soft loans for micro enterprises and cooperatives is carried out at PT.BPR BKK Lasem (Perseroda) reviewed the principle of caution in granting credit. Research results show that 1) In its implementation, the Rembang Regency Government has assigned BKK Lasem to provide stimulus from BUMD which can later be distributed to MSMEs and Cooperatives affected by Covid 19. 2) soft loans provided to Micro Enterprises and Cooperatives Affected by Covid-19 in Rembang Regency are operationally in the form of distribution of PT credit products. BPR BKK Lasem (Perseroda), namely Bangkit Micro Monthly Credit (KMB) with 0% (zero percent) interest, without collateral and no administration fees. Meanwhile, insurance and legalization costs are borne by PT. BPR BKK Lasem (Perseroda). The conclusion of this research is that the implementation of the Rembang Regent's Regulation Number 44 of 2020 relating to the provision of soft loans for Micro Enterprises and Cooperatives Affected by Covid-19 in Rembang Regency is a form of the Rembang Regency Government's commitment to regional economic recovery through the placement of APBD funds for operational subsidies to PT . BPR BKK Lasem (Persero) so that it can better carry out its function as a financial institution that can channel public funds effectively and efficiently, especially in credit services intended for Micro Enterprises and Cooperatives which are affected by the Covid-19 pandemic conditions and are hampered by collateral problems.